Membedah Semiotika dalam Iklan: Pendekatan Roland Barthes pada Iklan IM3 “Dekatkan Jarak, Nyatakan Silaturahmi“ - Fariardhany, Fakhrureza; Mihardja, Eli Jamilah (Calathu: Jurnal Ilmu Komunikasi, 2025)
The IM3 advertisement version of “Closer the distance, Declare the friendship” reveals certain connotations that can be in daily expressions and behaviors. The purpose of this research is to analyze the signs in the advertisement using Roland Barthes' semiotic approach. The method used is qualitative with the main data in the form of video advertisements downloaded from the official IM3 channel on YouTube. The results of the analysis showed that the visual and verbal elements in the advertisement successfully conveyed a message about the importance of communication and family closeness despite generational differences. The implication of this research is that the semiotic approach can enrich the understanding of communication strategies in advertising and can be used to improve the impact of advertising campaigns in the future.